Immunoblot Method To Detect Streptococcus pneumoniae and Identify Multiple Serotypes from Nasopharyngeal Secretions - Bronsdon, Melinda A. (American Society for Microbiology, 2004)
Conventional culture techniques are limited in the ability to detect multiple Streptococcus pneumoniae serotypes in nasopharyngeal (NP) secretions. We developed an immunoblot (IB) method with monoclonal antibodies (MAbs) to detect S. pneumoniae and to identify serotypes. NP specimens stored in skim milk-tryptone-glucose-glycerol medium were assessed by the IB method and the reference culture method (RM). In the RM, four optochin-sensitive alpha-hemolytic colonies resembling pneumococci were typed by the Quellung reaction. In the IB method, a nitrocellulose membrane blot of surface growth was reacted with a pneumococcal surface adhesion (PsaA) MAb and visualized. Of 47 NP specimens, 32 (68%) were found to be positive and 13 (28%) were found to be negative for pneumococci by both methods; each method alone yielded one positive result. The sensitivity and specificity of the IB method for the detection of pneumococci were 97 and 93%, respectively. To identify serotypes, blots were tested with serotype-specific MAbs (4, 6A, 6B, 9V, 14, 18C, 19F, and 23F). To detect the remaining serotypes, positive serotype-specific replicate blots were compared visually to an original anti-PsaA-positive blot; four unidentified colonies were subcultured and serotyped by the Quellung reaction. Fifty-eight S. pneumoniae-positive NP specimens containing 69 pneumococcal strains (23 serotypes) were tested; 68 (98.6%) of the strains were detected by the IB method, and 66 (95.6%) were detected by the RM. For 11 specimens found to contain two serotypes, both methods detected both serotypes in 7 (63.6%), the IB method alone detected the two serotypes in 3 (27.3%), and the RM alone detected both serotypes in 1 (9%). The IB method identified multiple clones and minor populations of pneumococci in NP secretions. This method is useful for detecting specific serotypes and carriage of multiple serotypes in epidemiologic surveillance and carriage studies.